Do Women Supply More Public Goods than Men? Preliminary Experimental Evidence from Matrilineal and Patriarchal Societies - Andersen, Steffen; Bulte, Erwin; Gneezy, Uri; List, John A (American Economic Review, 2008)
Do Women Supply More Public Goods Than Men? Preliminary Experimental Evidence from Matrilineal and Patriarchal Societies by Steffen Andersen, Erwin Bulte, Uri Gneezy and John A. List. Published in volume 98, issue 2, pages 376-81 of American Economic Review, May 2008